Kajian Etika Digital terhadap Peran Perempuan sebagai Content Creator Rohani di GPIB ATK - Abel, Jesica Lionita; Ludji, Irene; Paat, Gilbert (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2025)
The rapid development of technology over time has an impact on the role of women in their ministry in the congregation and society, especially in utilizing digital platforms to spread spiritual content and positive messages to the congregation and society. This study examines the role of women as spiritual content creators in the GPIB ATK Ambarawa Congregation within the framework of Kate Ott's feminist ethics. Through in-depth interviews with female content creators and analysis of the content they produce, this study explores how women in GPIB ATK utilize digital platforms to spread spiritual content and how they apply the principles of digital ethics in these activities. The results of the study indicate that women in GPIB ATK have a significant role in spreading positive messages through digital platforms. However, this study also identifies challenges associated with the use of digital technology, such as the spread of invalid information, potential privacy violations, and the social impact of the content they produce. Based on Kate Ott's feminist ethics theory, this study concludes that efforts are needed to improve women's digital literacy so that they can use technology responsibly and ethically. Thus, good digital literacy allows women not only to be consumers of information, but can also be agents of positive change in strengthening spirituality and morality in the digital era.